Unlocking Meaning : A Semantic Analysis of Denotation and Connotation in Langton Hughes' Poetry - Rudianto, Alfina Damayanti; Andriani, Zulfi Zumala Dwi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This article discusses a semantic analysis of the denotative and connotative meanings in three poems by Langston Hughes: "Dreams," "Mother to Son," and "Harlem." The research uses a qualitative descriptive approach with the theoretical framework of meaning by Geoffrey Leech (1981) and the semiotic approach of Daniel Chandler (2007). The analysis results show that each poem not only conveys individual aspirations and challenges but also represents the collective condition of marginalized communities. The connotative meanings of words and metaphors in the poems serve as a form of resistance to social oppression, implying resilience and emotional depth rooted in a history of struggle. Thus, this study demonstrates that literary works are not only a medium for artistic expression but also an instrument that responds to social injustice and inspires collective awareness in the fight for freedom.